The narrative of visual literacy: a framework for understanding the personal, social, and diachronic aspects of learning. Issue 1 (2nd January 2018) - Carter, Danielle
Abstract: In an environment that encourages co-construction and participatory practices, and especially in an educational environment saturated with media and images in which children are considered to be valid and competent contributors to knowledge construction, children's visual literacy becomes increasingly important to the development of educational theories and practice. In this paper, I focus on Visible Thinking as a reflective process through which students learn and which provides students with a metacognition of visual literacy; as students make their thinking visible and are guided to reflect upon these visual expressions, not only is their visual literacy developed, but so is their understanding of their thinking processes. Moreover, I argue that the emergent nature of learning can best be understood by using narrative as a framework to understand the personal, social and diachronic qualities of the learning process. Through the partnered use of Visible Thinking and narrative, teachers and researchers alike can gain a better understanding of the development of students' development of visual literacy as well as learning in a broader sense over time, through space, and across disciplines.